Pengaruh Customer Relationship Marketing dan Personal Selling terhadap Penjualan Produk di PT Amoeba Biosintesa Bandung - Bayu Dermawan; Nurhayati Nurhayati (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study was conducted to determine the effect of Customer Relationship Marketing and Personal Selling on increasing sales at PT Amoeba Biosintesa. Research using quantitative methods. Data collection using a 1-5 Likert scale questionnaire, data analyzed using SPSS software. The sample consisted of 100 respondents determined through the Lemeshow formula. The results show that simultaneously and partially Customer Relationship Marketing and personal selling simultaneously and partially have a positive and significant effect on increasing product sales at PT Amoeba Biosintesa. The coefficient of determination shows that Customer Relationship Marketing and Personal Selling contribute 59.6% to the increase in sales. Customer Relationship Marketing and Personal Selling play an important role in marketing strategy and have a significant influence on product sales at PT Amoeba Biosintesa. It is expected that the company optimizes Customer Relationship Marketing with advanced technology and service personalization, and increases the effectiveness of Personal Selling through training and direct interaction with customers.